Borna disease virus circulating immunocomplex positivity and psychopathology in psychiatric patients in the Czech Republic - Rackova, Sylva; Janu, Lubos; Kabickova, Hana (Neuro endocrinology letters, 2009)
OBJECTIVES: Borna disease virus (BDV) is an RNA virus belonging to the family Bornaviridae. BDV is a neurotropic virus that causes changes in mood, behaviour and cognition. Patients with psychiatric disorders have a higher incidence of BDV positivity than healthy individuals. METHODS: We examined the seropositivity of BDV circulating immunocomplexes (CIC) in psychiatric patients and healthy individuals (blood donors). We examined 39 psychiatric inpatients for the presence of BDV CIC in the serum by ELISA on day 0, 28 and 56. During the same period psychopathology was measured using psychiatric scales (CGI, CGI-I, MADRS, SDS, PANSS). This is the first such study performed in the Czech Republic. RESULTS: BDV CIC positivity was detected in 66.7% of psychiatric patients (26/39) on day 0, in 53.9% (14/26) on day 28 and in 52.9% on day 56 (9/17). The control group was 22.2% (28/126) positive. The incidence of BDV CIC was significantly higher in psychiatric patients than in healthy individuals (p=0.001). The significantly higher level of BDV CIC was associated with the higher severity of psychopathology in comparison with patients with mild or moderate psychopathology (p=0.03). We did not find any association between BDV CIC positivity and other characteristics (age, diagnosis, family, personal history, the history of infectious diseases, contact with animals). CONCLUSION: In our study psychiatric patients had significantly higher levels of BDV CIC than the control group. The highest levels of BDV CIC were detected in patients with more severe psychopathology.
Keywords: Borna disease virus; psychiatrické posuzovací škály; Blood Donors; Psychiatric Status Rating Scales; Schizophrenia; Time Factors; Česká republika; bornaská nemoc; Middle Aged; Mood Disorders; mužské pohlaví; Antibodies, Viral; poruchy nálady; Adult; RNA, Viral; Czech Republic; ženské pohlaví; ELISA; psychotické poruchy; Humans; Schizophrenic Psychology; časové faktory; lidé středního věku; schizofrenie; protilátky virové; schizofrenie (psychologie); Enzyme-Linked Immunosorbent Assay; dospělí; dárci krve; Psychotic Disorders; virus bornaské nemoci; Female; RNA virová; Borna Disease; lidé; Male